Influence Analysis of the Teacher Ratio and Facilities on Failure to Pass the Class Using Multiple Linear Regression - Suni, Eugenius Kau; Sutresno, Stephen Aprius; Christanto, Henoch Juli; Singgalen, Yerik Afrianto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The quality of education needs to be observed and maintained in building an effective teaching and learning environment. There are several factors that can affect the quality of education in a school, such as the availability of human resources, supportive learning facilities, environmental conditions, and various other factors. The focus of this research is on the ideal number of teachers in a school, considering the number of students and the availability of facilities such as laboratories and libraries, which will be correlated with the failure to pass the class rate. Data were obtained from the official website of the Kemdikbudristek regarding educational statistics, comprising 29 districts in Tangerang Regency for the academic year 2023/2024 at the senior high school level. The analysis was conducted using multiple linear regression, and it was found that the variables